ANALYZING THE SIGNIFIER AND SIGNIFIED OF HYPERBOLE IN KATY PERRY’S SONGS - Christo Alobyaman Yabarmase (Musamus Journal of Language and Literature, 2022)
The aim of this study was to analyze the signifier and signified of hyperbole in three songs by Katy Perry's, they are Firework, Rise, and Roar. This study applied a qualitative descriptive method with a semiotic approach by De Saussure that is used to understand the sign (signifier) ​​of a sentence and understand the meaning (signified) in the hyperbole. The data collection techniques used were library study, highlighting the hyperbole, and determining the signifier and signified parts of the hyperbole in song lyrics. It was found out that there are four hyperboles in Firework. This song conveys messages about the virtue of remaining confident, loving ourselves, and having a positive impact upon everyone else. In Rise, there were four data of hyperbole. It conveys a message encouraging us to maintain our confidence and belief in our genuine identity. Lastly, Roar consisted of three hyperbole data. It sends out a message of encouragement to us to remain brave and capable of defining our identity towards those who constantly underestimate others